The Effect of Entrepreneurs' Gender and Gendered Startup Fields on Organizational Attraction for Potential Applicants - Marissa Ofir (Junior Management Science (JUMS), 2023)
Entrepreneurship is growing, and thereby applicants are more often presented with the opportunity to work in a start-up. Simultaneously, a lack of gender diversity in start-up leadership has been reported, and gender stereotyping has manifested itself in the entrepreneurial world. These developments motivate further studies on how potential applicants are attracted to start-ups. In this study, I examine the effect that the entrepreneur's gender and gendered start-up field has on potential applicants' organizational attraction to the company. The present study investigates four fabricated start-ups: 1. Male founder of a technology start-up, 2. Male founder of a sustainable start up, 3. Female founder of a technology start-up, and 4. Female founder of a sustainable start up, where participants are randomly selected to reveal through an online experiment their intent to pursue the start-up. Data from 246 prospective graduates, graduates, and young professionals indicates that the start-up field is more valuable when considering one's organizational attraction to a company than the entrepreneur's gender. Unforeseeably, both the female and male participants preferred a sustainable context start-up, but with varying founder gender preferences.
Keywords: 650; Entrepreneurship; Gender stereotypes; Applicant recruitment; Organizational attraction